Third Five-Year Plan of Tumkur District - Planning Commission (Planning Commission, 1963)
The Third Plan envisages a magnitude of effort which is much greater than that of the previous Plan. The crucial test, however, lies in its implementation. For a full realisation of its benefits, the Plan has to be implemented with the highest possible efficiency at all levels especially so at the levels of the District, Block and Village. For, it is in these areas of activity that a wide range of plan programmes is translated into its concrete physical shape.
Planning, Housing and Social Welfare Department Government of Mysore